Implementasi Kampus Mengajar Angkatan 6 di SMPN 1 Titehena - Margiana Dewi Maria Madonna Maran (Journal on Education, 2024)
Kampus Mengajar is part of the learning and teaching activities in the basic education unit of the Merdeka Belajar Kampus Merdeka (MBKM) program as an effort to provide opportunities for students to learn outside the classroom by becoming teacher partners in the learning process in primary and secondary education units, hereinafter referred to as assignment schools. Kampus Mengajar is part of the Merdeka Belajar Kampus Merdeka (MBKM) program which aims to help primary and secondary schools affected by the COVID-19 pandemic. One of the target schools for the Batch 6 Kampus Mengajar program is SMPN 1 Titehena which is located in Lewolaga Village, Titehena District, East Flores Regency, East Nusa Tenggara. The purpose of this study is to determine the implementation of the Batch 6 Kampus Mengajar program at SMPN 1 Titehena related to the Kampus Mengajar program, namely literacy, numeracy, technology adaptation and school administration. The research method used in this study is descriptive qualitative using data collection techniques in the form of observation and interviews with research subjects. The results of the study were analyzed using the theory of Miles and Huberman, namely data collection, data reduction, data presentation and conclusion drawing. The results show that the implementation of the Batch 6 Kampus Mengajar program is very beneficial for schools in improving literacy, numeracy, technology adaptation and school administration at SMPN 1 Titehena. The Batch 6 Kampus Mengajar program proved successful in improving students' literacy and numeracy at SMPN 1 Titehena. The involvement of teachers in collaborating with the Kampus Mengajar and innovative learning methods contributed positively to the development of learning strategies. The implementation of the Batch 6 Kampus Mengajar program is an inspiring model in addressing the complex challenges of education.